Comparative study of pyloromyotomy by laparoscopic and conventional surgery in dogs: MJ Eesa, A A Ajeel , A K Mahdi and H H Nahi - Eesa, M. J. (The Iraqi Journal of Veterinary Medicine, 2012)
Pyloromyotomy is a procedure to increase the diameter of pyloric region, routinely performed during pyloric stenosis to prevent delayed emptying of stomach content. The aim of this study was to evaluate the pyloromyotomy by conventional and laparoscopic techniques. Ten adult healthy dogs were used. Five animals underwent the pyloromyotomy by conventional and the same number laparoscopic technique. The clinical radiological and laparoscopic results of two techniques revealed that both were successive for achieved this purpose, but the laparoscopic pyloromoytomy characterized by small abdominal incision minimal adhesion and rapid healing.